2020
DOI: 10.13189/cea.2020.080518
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration as a Tool for Enhancing Vitality of Urban Spaces

Abstract: The recent discussion regarding contemporary urban regeneration has underlined its increasing role to revive cities. In the mid-19th century, the process of urban regeneration commenced through upgrading the already built areas, particularly where there is evidence of urban deterioration. This study by using qualitative grounded theory, hypothesized that attaining an effective urban regeneration involves an increasing quality of life and vitality. The study revealed that a successful urban regeneration involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The public squares had been treated with special attention; they were provided with pavements, freshwater, plants, and street furnishings [17]. Equity in distributions of urban public infrastructure is the dominant objective for regenerating public urban spaces by referring to people [23].…”
Section: Urban Windowsmentioning
confidence: 99%
“…The public squares had been treated with special attention; they were provided with pavements, freshwater, plants, and street furnishings [17]. Equity in distributions of urban public infrastructure is the dominant objective for regenerating public urban spaces by referring to people [23].…”
Section: Urban Windowsmentioning
confidence: 99%
“…Scientists who focus on this research are primarily found in countries with higher urbanism and industrialization, such as the USA, China, and Germany [5,6]. Development, sustainable development, pillars of sustainable development and other realities are directly or indirectly linked to the soil as a resource, space, and economic factor [7,8]. The revitalization of brownfields is a logical step towards achieving the sustainability of the territory.…”
Section: Introductionmentioning
confidence: 99%
“…Its use, especially for trading activities, is usually with low supervision and this causes the risk of losing the space due to the expropriation of rights by traders [10] and [11]. Moreover, the unofficial and unplanned change and takeover of the spatial functions have an impact on the environment [12] due to the fact that the informal activities usually conducted in the space have the ability to change its social and cultural conditions [13] and influence image of a Street [14]. Meanwhile, the limited availability of infrastructures caused by rapid and unplanned urban growth negatively affects traders through the pressure from formal and non-formal actors [15] and low levels of security [16].…”
Section: Introductionmentioning
confidence: 99%